2020
DOI: 10.3390/s20051484
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sensor Data and Health Monitoring for Early Detection of Subclinical Ketosis in Dairy Cows

Abstract: Subclinical ketosis is a metabolic disease in early lactation. It contributes to economic losses because of reduced milk yield and may promote the development of secondary diseases. Thus, an early detection seems desirable as it enables the farmer to initiate countermeasures. To support early detection, we examine different types of data recordings and use them to build a flexible algorithm that predicts the occurence of subclinical ketosis. This approach shows promising results and can be seen as a step towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The system algorithm calculated the time difference of arrival-that is, the time it took the signal to travel from the ear tags to at least 4 receivers and triangulate the location of the cow within the barn. Further information on the localization feature of the SB system is found in Byrne et al (2019) and Sturm et al (2020).…”
mentioning
confidence: 92%
“…The system algorithm calculated the time difference of arrival-that is, the time it took the signal to travel from the ear tags to at least 4 receivers and triangulate the location of the cow within the barn. Further information on the localization feature of the SB system is found in Byrne et al (2019) and Sturm et al (2020).…”
mentioning
confidence: 92%
“…Activity (59.42%, p < 0.001), down time (45.40%, p < 0.001) and activity change (77.78%, p < 0.001) were lower in HG (Figure 1). Sturm et al 2020 [16] reported that cows at risk for SKC are slower, i.e., fewer moves compared to healthy cows. Long lying times and a reduction in activity (i.e., paresis) are common sickness behaviours and are clinical symptoms of milk fever [17].…”
Section: Resultsmentioning
confidence: 99%
“…of previous studies concerned sensors-based validations [15,40,41], observations of physiological behaviors [20,42,43] or comparison between PDF technologies outputs and the available animals' health parameters derived from the farms' databases [29,44,45], only a few studies focused on a strict comparison between the devices' output and individual clinical-diagnostic activities [46][47][48], such as performed in the current investigation (Fig 1 and Supplementary file-S3 Table ).…”
Section: Plos Onementioning
confidence: 99%